Method for improving electrical properties of silicon carbide-metal composite interface
Femtosecond laser annealing improves the silicon carbide-metal composite interface by forming SiOx and graphene structures, addressing the limitations of traditional methods and enhancing electrical properties and stability.
Patent Information
- Application Number
- CN202410975058.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-07-19
AI Technical Summary
Existing methods to improve the silicon carbide-metal composite interface, such as ion implantation and high-temperature annealing, cause lattice distortion or damage, affecting the stability and electrical properties of semiconductor devices.
Femtosecond laser annealing is used to optimize the silicon carbide surface, inducing a phase change and generating plasma to form SiOx and graphene structures, improving carrier concentration and conductivity while maintaining structural stability through spatial selectivity.
The method enhances the electrical properties of the silicon carbide-metal composite interface by increasing carrier concentration and conductivity, reducing the Schottky barrier, and maintaining device stability with minimal damage to non-modified areas.
Smart Images

Figure CN119181633A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor devices, and in particular relates to a method for improving the electrical performance of a silicon carbide-metal composite interface. Background Art
[0002] The development of semiconductor science and technology has promoted progress and change in all areas of society. At the same time, semiconductor materials are also the basis of computer, network and communication technology. Starting from the first generation of semiconductor silicon materials, with the continuous progress and maturity of the industrial industry, people are constantly seeking breakthroughs in material performance to meet the needs of different fields.
[0003] As one of the representatives of the third generation of semiconductor materials, silicon carbide has broad application prospects in the field of high-frequency and high-power devices due to its excellent physical and chemical stability. However, due to the complex surface state of silicon carbide, there are many unsaturated dangling bonds on its surface, which will change the energy state of the contact interface after contact with the metal electrode, resulting in a Schottky barrier, which will have a great impact on the stability of the device. Existing treatment methods often increase the carrier concentration or reduce the Schottky barrier to obtain more stable contact interface properties. The corresponding methods are ion implantation and high-temperature annealing. However, ion implantation will inevitably cause lattice distortion or loss of the material, and high-temperature annealing will also cause certain damage to the non-modified area of the device, which also affects the device life. Therefore, it is very necessary to develop new methods to improve the electrical properties of the silicon carbide and metal contact interface. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for improving the electrical properties of a silicon carbide-metal composite interface in view of the above-mentioned deficiencies in the prior art. The surface of the silicon carbide material is annealed by optimizing process parameters using femtosecond laser technology. The obtained annealed surface not only has a higher carrier concentration and conductivity, but also the spatial selectivity of the femtosecond laser ensures the stability of the structure of the non-modified region. The method is simple to operate.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] A method for improving the electrical properties of a silicon carbide-metal composite interface is provided, and the specific steps are as follows:
[0007] 1) Cleaning and drying the single crystal silicon carbide substrate to obtain a clean single crystal silicon carbide substrate;
[0008] 2) placing the clean single-crystalline silicon carbide substrate obtained in step 1) on a laser galvanometer processing platform, and annealing the surface of the single-crystalline silicon carbide substrate using a femtosecond laser. After the annealing is completed, a metal layer is prepared on the surface of the single-crystalline silicon carbide substrate as needed.
[0009] According to the above scheme, the single crystal silicon carbide substrate in step 1) is one of an N-type 4H-SiC substrate, a 3C-SiC substrate, and a 6H-SiC substrate.
[0010] According to the above scheme, the process conditions for annealing the surface of the single-crystal silicon carbide substrate using a femtosecond laser in step 2) are: a femtosecond laser wavelength of 1030 nm, a repetition frequency of 200 kHz, a pulse width of 260 fs, and a laser flux of 0.2 to 1.4 J / cm 2 , the scanning speed is 10-100 mm / s, and the scanning interval is 5-20 μm.
[0011] Preferably, the process conditions for annealing the surface of the single crystal silicon carbide substrate using a femtosecond laser in step 2) are: a femtosecond laser wavelength of 1030 nm, a repetition frequency of 200 kHz, a pulse width of 260 fs, and a laser flux of 0.6 J / cm 2 , the scanning speed is 50mm / s, and the scanning spacing is 10μm.
[0012] According to the above scheme, the method of preparing the metal layer on the surface of the single crystal silicon carbide substrate in step 2) is: preparing it by vacuum evaporation.
[0013] Preferably, the metal layer is a gold electrode layer with a thickness of 50 to 100 nm.
[0014] The present invention also includes a semiconductor device obtained by the above method.
[0015] The present invention utilizes femtosecond laser annealing to induce a phase change on the SiC surface through a photochemical reaction, so that the original Si-C bonds on the surface of the material are opened, generating plasma, in which a part of the Si element reacts with the O element in the air to generate SiO x The structure is amorphous Si, part of which exists in the form of amorphous Si and is deposited on the modified surface. C is induced by laser to produce graphene structure on the modified SiC surface. Among them, SiO containing O vacancy defects x The structure significantly improves the interface carrier concentration, and the generated graphene structure changes the bandgap width of the original material and the electrode contact surface, improves the electrical transport characteristics of the SiC and metal interface, increases the current size, and improves the stability of the device. At the same time, femtosecond laser annealing combines the advantages of high-temperature annealing and ion implantation, using the high spatial selectivity of the laser to avoid the defects caused by thermal annealing in the non-modified area, while optimizing the process flow, which is more efficient and simpler than traditional annealing.
[0016] The beneficial effects of the present invention are as follows: the method provided by the present invention can effectively improve the electrical properties of the silicon carbide-metal composite interface, and the carrier concentration and conductivity of the obtained sample are greatly improved. The method is simple to operate and is more efficient than the traditional annealing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The surface SEM images of the clean single crystal SiC substrate obtained in step 1) of the embodiment and the single crystal SiC substrate annealed under different laser fluxes in step 2);
[0018] Figure 2 The laser flux for Example 1 is 0.6 J / cm 2 Cross-sectional SEM image of the single crystal SiC substrate annealed under low temperature;
[0019] Figure 3 Surface Raman spectra of the clean single crystal SiC substrate (denoted as Pristine) obtained in step 1) of Example 1 and the single crystal SiC substrate annealed under different laser fluxes in step 2);
[0020] Figure 4 The volt-ampere characteristic curves of the five samples obtained in Example 2;
[0021] Figure 5 The volt-ampere characteristic curves of the four samples obtained in Example 3;
[0022] Figure 6 The volt-ampere characteristic curves of the four samples obtained in Example 4;
[0023] Figure 7 The volt-ampere characteristic curves of the four samples obtained in Example 5;
[0024] Figure 8 The Schottky barrier comparison diagram of the samples obtained by evaporating gold electrodes on the surface of SiC substrates annealed under different laser fluxes and clean single crystal SiC substrates without annealing;
[0025] Fig. 9 The comparison diagram of carrier concentration on the surface of a clean single crystal SiC substrate without annealing treatment and the surface of a SiC substrate obtained under the optimal annealing process parameters;
[0026] Fig.10 The conductivity comparison diagram of a clean single crystal SiC substrate without annealing treatment and a SiC substrate obtained under the optimal annealing process parameters;
[0027] Fig.11 The EDS spectra of a clean single crystal SiC substrate without annealing and a SiC substrate obtained under the optimal annealing process parameters;
[0028] Fig.12 This is a comparison chart of XPS energy spectrum tests of a clean single crystal SiC substrate that has not been annealed and a SiC substrate obtained under the optimal annealing process parameters. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0030] Example 1
[0031] A method for improving the electrical properties of a silicon carbide-metal composite interface, the specific steps are as follows:
[0032] 1) Five N-type 4H-SiC substrates with a thickness of 500 μm were ultrasonically cleaned with ethanol and deionized water for 15 minutes respectively, and then dried in an oven at 60° C. for 40 minutes to obtain clean single crystal SiC substrates;
[0033] 2) Take 4 single crystal SiC substrates obtained in step 1) and place them on the laser galvanometer processing platform respectively, and turn on the femtosecond laser to anneal the surface of the single crystal SiC substrate. The femtosecond laser wavelength used is 1030nm, the repetition frequency is 200kHz, the pulse width is 260fs, and the laser flux is controlled to be 0.2J / cm 2 , 0.6J / cm 2 , 1.0J / cm 2 , 1.4J / cm 2 , scan at a speed of 100 mm / s with a scanning interval of 10 μm. After completing laser annealing, remove the SiC substrate.
[0034] The surfaces of the clean single crystal SiC substrate obtained in step 1) of this embodiment and the single crystal SiC substrate annealed under different laser fluxes in step 2) were analyzed by scanning electron microscope. The SEM images are as follows: Figure 1 As shown in the figure, (a) is the SEM image of the clean single crystal SiC substrate surface obtained in step 1), (b), (c), and (d) are respectively the SEM images of the surface of the clean single crystal SiC substrate obtained in step 2) with a laser flux of 0.2 J / cm 2 , 0.6J / cm 2 , 1.0J / cm 2 SEM images of the surface of a single-crystal SiC substrate annealed under low temperature. (e) and (f) are images of the surface of a single-crystal SiC substrate annealed under low temperature with a laser flux of 1.4 J / cm 2 SEM image of the surface of the single crystal SiC substrate annealed under low temperature. It can be seen that the laser flux is 0.2J / cm 2 The surface modification effect of the substrate is not obvious, and the laser flux is too large (1.4J / cm 2 ) will produce amorphous clusters on the substrate surface, resulting in the formation of modified layers with different orientations on the surface. The appropriate laser flux is 0.6-1.0 J / cm 2 .
[0035] Figure 2 The laser flux is 0.6 J / cm 2From the cross-sectional SEM image of the single-crystal SiC substrate annealed at 400 nm, it can be seen that the laser annealing treatment forms a modified layer with a thickness of 3 μm on the surface of the single-crystal SiC substrate.
[0036] Figure 3 Figure 1 is the surface Raman spectra of the clean single crystal SiC substrate (denoted as Pristine) obtained in step 1) of this embodiment and the single crystal SiC substrate annealed under different laser fluxes in step 2). It can be seen that with the increase of laser flux, SiO with O vacancy defects is generated on the surface of the single crystal SiC substrate. x structure and graphite structure.
[0037] Example 2
[0038] A method for improving the electrical properties of a silicon carbide-metal composite interface, the specific steps are as follows:
[0039] 1) Five N-type 4H-SiC substrates with a thickness of 500 μm were ultrasonically cleaned with ethanol and deionized water for 15 minutes respectively, and then dried in an oven at 60° C. for 40 minutes to obtain clean single crystal SiC substrates;
[0040] 2) Take 4 single crystal SiC substrates obtained in step 1) and place them on the laser galvanometer processing platform respectively, and turn on the femtosecond laser to anneal the surface of the single crystal SiC substrate. The femtosecond laser wavelength used is 1030nm, the repetition frequency is 200kHz, the pulse width is 260fs, and the laser flux is controlled to be 0.49J / cm 2 , 0.55J / cm 2 , 0.61J / cm 2 , 0.67J / cm 2 , scanning at a speed of 100 mm / s and a scanning interval of 5 μm. After laser annealing, the SiC substrate is removed and 80 nm thick gold electrodes are evaporated on the surfaces of four annealed SiC substrates and a clean single crystal SiC substrate that has not been annealed by vacuum evaporation.
[0041] The volt-ampere characteristic curves of the five samples obtained in this embodiment are tested, and the obtained IV curves are shown in FIG. Figure 4 As shown in the figure, it can be seen that the Schottky barrier of the sample obtained without annealing treatment at the Au / SiC interface is higher, and the Schottky barrier of the sample obtained after laser annealing at the Au / SiC interface is reduced, that is, compared with the SiC substrate without annealing treatment, the electrical properties of the SiC substrate after laser annealing are improved. The laser flux is 0.61J / cm 2 The electrical performance is the best when the laser flux increases. After that, the electrical performance decreases.
[0042] Example 3
[0043] A method for improving the electrical properties of a silicon carbide-metal composite interface, the specific steps are as follows:
[0044] 1) Four N-type 4H-SiC substrates with a thickness of 500 μm were ultrasonically cleaned with ethanol and deionized water for 15 minutes, and then dried in an oven to obtain clean single crystal SiC substrates;
[0045] 2) The single crystal SiC substrates obtained in step 1) were placed on the laser galvanometer processing platform, and the femtosecond laser was turned on to anneal the surface of the single crystal SiC substrate. The femtosecond laser wavelength used was 1030nm, the repetition frequency was 200kHz, the pulse width was 260fs, and the laser flux was controlled to be 0.49J / cm 2 , 0.55J / cm 2 , 0.61J / cm 2 , 0.67J / cm 2 , scanning at a speed of 100 mm / s and a scanning interval of 10 μm. After laser annealing, the SiC substrate is removed and 80 nm thick gold electrodes are evaporated on the surface of the four annealed SiC substrates by vacuum evaporation.
[0046] The volt-ampere characteristic curves of the four samples obtained in this embodiment are tested, and the obtained IV curves are shown in FIG. Figure 5 As shown, it can be seen that the laser flux is 0.61J / cm 2 The electrical properties of the sample annealed at 500 nm were the best. After that, when the laser flux increased further, the slope of the sample curve dropped and the Schottky barrier rose again.
[0047] Example 4
[0048] A method for improving the electrical properties of a silicon carbide-metal composite interface, the specific steps are as follows:
[0049] 1) Four N-type 4H-SiC substrates with a thickness of 500 μm were cleaned by ultrasonic cleaning with ethanol and deionized water, and then dried in an oven to obtain clean single crystal SiC substrates;
[0050] 2) The single crystal SiC substrates obtained in step 1) were placed on the laser galvanometer processing platform, and the femtosecond laser was turned on to anneal the surface of the single crystal SiC substrate. The femtosecond laser wavelength used was 1030nm, the repetition frequency was 200kHz, the pulse width was 260fs, and the laser flux was controlled to be 0.49J / cm 2 , 0.55J / cm 2 , 0.61J / cm 2 , 0.67J / cm 2, scanning at a speed of 100 mm / s and a scanning interval of 15 μm. After laser annealing, the SiC substrate is removed and 80 nm thick gold electrodes are evaporated on the surface of the four annealed SiC substrates by vacuum evaporation.
[0051] The volt-ampere characteristic curves of the four samples obtained in this embodiment are tested, and the obtained IV curves are shown in FIG. Figure 6 As shown, it can be seen that the laser flux is 0.61J / cm 2 The electrical properties of the sample annealed at 500 nm were the best. After that, when the laser flux increased further, the slope of the sample curve dropped and the Schottky barrier rose again.
[0052] Example 5
[0053] A method for improving the electrical properties of a silicon carbide-metal composite interface, the specific steps are as follows:
[0054] 1) Four N-type 4H-SiC substrates with a thickness of 500 μm were cleaned by ultrasonic cleaning with ethanol and deionized water, and then dried in an oven to obtain clean single crystal SiC substrates;
[0055] 2) The single crystal SiC substrates obtained in step 1) were placed on the laser galvanometer processing platform, and the femtosecond laser was turned on to anneal the surface of the single crystal SiC substrate. The femtosecond laser wavelength used was 1030nm, the repetition frequency was 200kHz, the pulse width was 260fs, and the laser flux was controlled to be 0.49J / cm 2 , 0.55J / cm 2 , 0.61J / cm 2 , 0.67J / cm 2 , scanned at a speed of 50 mm / s (equivalent pulse number N=100) with a scanning interval of 10 μm. After laser annealing, the SiC substrate was removed and 80 nm thick gold electrodes were evaporated on the surfaces of the four annealed SiC substrates by vacuum evaporation.
[0056] The volt-ampere characteristic curves of the four samples obtained in this embodiment are tested, and the obtained IV curves are shown in FIG. Figure 7 As shown, it can be seen that the laser flux is 0.61J / cm 2 The electrical properties of the sample annealed at 500 nm were the best. After that, when the laser flux increased further, the slope of the sample curve dropped and the Schottky barrier rose again.
[0057] From the above examples, it can be seen that the most preferred annealing process parameters are: laser wavelength of 1030nm, repetition frequency of 200kHz, pulse width of 260fs, laser flux of 0.61J / cm 2, the scanning interval is 10μm, and the scanning speed is 50mm / s. The Hall effect test of the annealed sample obtained under this condition shows that the carrier concentration on the SiC surface (Si surface) after femtosecond laser annealing reaches 1.77×10 18 cm -3 , the conductivity reached 0.56×10 1 S / m, the Schottky barrier at the interface with the gold electrode is 0.69 eV, while the carrier concentration on the surface of the clean single-crystal SiC substrate (Si surface) without annealing is 5.40×10 13 cm -3 , the conductivity is 1.71×10 -4 S / m, and the Schottky barrier at the interface in contact with the gold electrode is 1.43 eV, indicating that the method for improving the electrical properties of the silicon carbide-metal composite interface of the present invention can greatly improve the electrical properties of the silicon carbide interface.
[0058] The method of Example 1 was used for testing, except that the scanning speed was 50 mm / s. Then, 80 nm thick gold electrodes were deposited on the surfaces of the four annealed SiC substrates and the clean single crystal SiC substrate without annealing by vacuum evaporation, and the volt-ampere characteristic curves of the five samples were tested. The comparison of the Schottky barriers of the five samples is shown in FIG. Figure 8 As shown in the figure, it can be seen that the SiC substrate has a laser flux of 0.6J / cm 2 The Schottky barrier height of the sample obtained during annealing is the lowest, and the energy required for electrons to pass from semiconductor to metal is the lowest, that is, the laser flux is 0.6 J / cm 2 The electrical properties of the SiC substrate annealed at around 5000 Å are the best.
[0059] Fig. 9 The figure shows the comparison of the carrier concentration on the surface of a clean single crystal SiC substrate (denoted as the original sample) without annealing treatment and the surface of a SiC substrate obtained under the optimal annealing process parameters (denoted as the femtosecond laser annealed sample). The results show that compared with the SiC substrate without annealing treatment, the carrier concentration of the SiC substrate sample after laser annealing is significantly improved, that is, the SiC substrate sample after laser annealing has a higher carrier mobility.
[0060] The conductivity of a clean single-crystal SiC substrate without annealing (referred to as the original sample) and a SiC substrate obtained under the optimal annealing process parameters (referred to as the femtosecond laser annealing sample) was tested by the four-probe method. The comparison diagram is shown in Fig.10 Compared with the SiC substrate without annealing, the electrical conductivity of the SiC substrate sample after laser annealing is greatly improved.
[0061] Fig.11The clean single crystal SiC substrate without annealing (denoted as Pristine) and the SiC substrate obtained under the optimal annealing process parameters (denoted as 0.61 J / cm 2 ) and statistically analyzed the percentage of each element content. It was found that the surface of the clean single-crystal SiC substrate without annealing had almost only carbon and silicon. After femtosecond laser annealing, the oxygen content on the substrate surface increased significantly, from 0.83% to 17.01%. Correspondingly, the relative carbon content on the surface decreased significantly. Laser annealing makes the oxygen element evenly cover the modified surface. This uniform oxygen distribution is conducive to the stability of subsequent device performance.
[0062] In order to further explore the effect of annealing on the electron binding energy of SiC surface, the clean single crystal SiC substrate without annealing (denoted as Pristine) and the SiC substrate obtained under the optimal annealing process parameters (denoted as 0.61 J / cm 2 ) was tested by XPS spectrum, and the test results are shown in Fig.12 , where (a) compares the overall changes in the XPS energy spectra of the samples before and after laser annealing. The results show the peaks of silicon (Si 2p and Si 2s), carbon (C 1s) and oxygen (O 1s). The appearance of the oxygen peak of the original sample in the XPS full spectrum is attributed to the surface oxidation of 4H-SiC in an air environment. It can be seen that after laser annealing, the O1s peak intensity on the 4H-SiC surface is significantly enhanced, while the corresponding Si 2s, Si 2p and C1s peak intensities are weakened, which is a good proof that the O element from the air reacts with the carbon and silicon elements on the sample surface. (b) The peak position of the C1s orbital energy spectrum was calibrated. The peaks at 280.1eV and 282.2eV corresponded to the Si-C bond and CC bond, respectively. The presence of the CC bond may be caused by impurities during the growth process. After laser annealing, the peak corresponding to the Si-C bond disappeared, indicating that SiC was photodecomposed and the surface Si-C bonds were broken. The peak width corresponding to the CC bond at 282.2eV increased significantly, reflecting that the disorder of the surface C increased at this time, inducing the generation of different carbon structures. Figure 3The Raman test results confirm that the induced substance is a graphite structure. (c) The energy spectrum analysis of the Si 2p orbital before and after annealing shows that after annealing, the characteristic peak of the substrate corresponding to the intrinsic structure Si-C bond at 102.4eV disappears, and is replaced by two new peaks at 100.8eV and 103.5eV, corresponding to the Si-Si bond and Si-O bond, respectively. This indicates that under the influence of the laser, the surface of the SiC sample decomposes and undergoes an oxidation reaction, in which the Si-O bond comes from the high-energy Si plasma generated by the photochemical reaction, which reacts with oxygen in the air, and the Si-Si bond at 100.8eV indicates that the laser annealing simultaneously produces Si elemental. (d) The O1s orbitals of the 4H-SiC surface before and after annealing were calibrated and analyzed. Only Si-O bonds existed on the surface of the sample without femtosecond laser annealing, which represented the presence of SiO2. The source of SiO2 may be the oxide layer generated when the SiC surface was exposed to the atmosphere. After annealing, the characteristic peak of 533.2eV corresponding to SiO2 disappeared, while the characteristic peak corresponding to SiOx / Si compound was generated at 533.8eV, indicating that the laser annealing sample surface can induce the generation of non-stoichiometric SiOx / Si compounds with oxygen vacancy defects. The formation method can be expressed by the following formula:
[0063] SiC (s) +O 2(a) →SiO x(s) +Si (s) +C s +CO 2(a)
[0064] The formation of this compound is the cause of Fig.11 The main reason for the increase in the O content in the EDS spectrum is the introduction of oxygen, while the decrease in the carbon content is due to the introduction of oxygen on the one hand, and on the other hand, the breakage of the original Si-C bond during the annealing process may cause part of the C element or plasma to escape, or generate CO2 with oxygen in the air and volatilize. The overall change in silicon content is not large, which can be attributed to the fact that amorphous silicon is re-deposited on the surface of the sample and bonded with C and O. Since the peak of the Si-C bond is not observed in the XPS spectrum of the sample after laser annealing, it shows that the Si element generated by the breakage of the Si-C bond exists in the form of single crystal or SiOx / Si compound. At this time, the surface oxygen content will affect the SiOx / Si structure, and then when the O content is insufficient, O vacancy defects will be generated on the SiC surface, and this defect will affect the electrical transmission characteristics of the sample surface.
Claims
1. A method for improving the electrical properties of a silicon carbide-metal composite interface, characterized in that: The specific steps are as follows: 1) Cleaning and drying the single crystal silicon carbide substrate to obtain a clean single crystal silicon carbide substrate; 2) placing the clean single-crystalline silicon carbide substrate obtained in step 1) on a laser galvanometer processing platform, and annealing the surface of the single-crystalline silicon carbide substrate using a femtosecond laser. After the annealing is completed, a metal layer is prepared on the surface of the single-crystalline silicon carbide substrate as needed.
2. The method for improving the electrical properties of silicon carbide-metal composite interface according to claim 1, characterized in that: Step 1) The single crystal silicon carbide substrate is one of an N-type 4H-SiC substrate, a 3C-SiC substrate, and a 6H-SiC substrate.
3. The method for improving the electrical properties of silicon carbide-metal composite interface according to claim 1, characterized in that: Step 2) The process conditions for annealing the surface of the single crystal silicon carbide substrate using a femtosecond laser are as follows: the wavelength of the femtosecond laser is 1030nm, the repetition frequency is 200kHz, the pulse width is 260fs, and the laser flux is 0.2-1.4J / cm 2 , the scanning speed is 10-100 mm / s, and the scanning interval is 5-20 μm.
4. The method for improving the electrical properties of silicon carbide-metal composite interface according to claim 3, characterized in that: Step 2) The process conditions for annealing the surface of the single-crystal silicon carbide substrate using a femtosecond laser are as follows: the wavelength of the femtosecond laser is 1030nm, the repetition frequency is 200kHz, the pulse width is 260fs, and the laser flux is 0.6J / cm 2 , the scanning speed is 50mm / s, and the scanning spacing is 10μm.
5. The method for improving the electrical properties of silicon carbide-metal composite interface according to claim 1, characterized in that: Step 2) The method for preparing a metal layer on the surface of a single crystal silicon carbide substrate is: preparing it by vacuum evaporation.
6. The method for improving the electrical properties of silicon carbide-metal composite interface according to claim 1, characterized in that: The metal layer is a gold electrode layer with a thickness of 50 to 100 nm.
7. A semiconductor device obtained according to the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method for preparing high-quality semi-insulation silicon carbide monocrystalline substrate
CN109234802A
Method of fabricating metal silicide layer over silicon carbide substrate and semiconductor device including metal silicide layer
CN116387140A
Silicon carbide semiconductor device manufacturing method
JP2016046309A
Localized annealing of metal-silicon carbide ohmic contacts and devices so formed
US20050104072A1
Method for manufacturing a contact on a silicon carbide semiconductor substrate, and silicon carbide semiconductor device
US20240055256A1
Cited By
Silicon carbide spin defect preparation method based on femtosecond laser direct writing
CN120395114A
Method for repairing edge leakage of silicon carbide Schottky diode
CN122555437A
Method for repairing edge leakage of silicon carbide schottky diodes
CN122555437B
